Effect of Short-Duration Low-Magnitude Cyclic Loading Versus Immobilization on Tendon-Bone Healing After ACL Reconstruction in a Rat Model - Brophy, Robert H. (Journal of Bone and Joint Surgery, Inc., 2011)
BACKGROUND: Successful anterior cruciate ligament reconstruction with use of soft-tissue grafts requires healing between tendon and bone. Little is known about the effect of mechanical load on the cellular and molecular cascade of tendon-to-bone healing. Understanding these mechanical influences has critical implications for postoperative rehabilitation following anterior cruciate ligament reconstruction. The purpose of this study was to test the hypothesis that, compared with perioperative immobilization, short-duration low-magnitude cyclic axial loading would result in impaired tendon-to-bone healing after anterior cruciate ligament reconstruction in a rat model. METHODS: Fifty-two male Sprague-Dawley rats underwent anterior cruciate ligament reconstruction with use of a flexor digitorum longus autograft. The patellar tendon, capsule, and ligamentous structures were circumferentially released, and an external fixator parallel to the anterior cruciate ligament graft was placed across the knee. Mechanical loading, consisting of cyclic displacement of the femur and tibia constrained to axial translation parallel to the graft, was applied daily. The rats were randomly assigned to immobilization or daily loading, for fourteen or twenty-eight days. Biomechanical, micro-computed tomographic, and histomorphometric analysis was performed on the bone-tendon-bone complexes. RESULTS: The load measured across the knees during cyclic displacement increased over time (p < 0.05). Load-to-failure testing of the isolated femur-anterior cruciate ligament graft-tibia specimens revealed no significant differences between groups at two or four weeks. By two weeks postoperatively, a greater number of ED1+ inflammatory macrophages (phagocytic cells involved in the initial injury response) were seen at the tendon-bone interface after loading in the cyclically loaded group than in the immobilized group (p = 0.01). Compared with the baseline values, the number of trabeculae was significantly lower after loading for four weeks (p = 0.02). CONCLUSIONS: Short-duration low-magnitude cyclic axial loading of the anterior cruciate ligament graft in the postoperative period is not detrimental to the strength of the healing tendon-bone interface but appears to be associated with greater inflammation and less bone formation in the tunnel in this rat model. CLINICAL RELEVANCE: Further investigation of varied timing and magnitude of graft-loading may help guide postoperative rehabilitation protocols following anterior cruciate ligament reconstruction with soft-tissue grafts.